2010
DOI: 10.1007/s12098-010-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistent diarrhea: Risk factors and outcome

Abstract: The presence of these risk factors should alert the clinician to take appropriate measures, to decrease the mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
2
18
0
4
Order By: Relevance
“…Inadequate dietary intake weakens the responses of the immune system in children and increases vulnerability to infections. Several studies have been confirmed that infections were commonly diagnosed in children suffering from undernutrition [44, 45]. Another study identified that soil of the plantation sector of Sri Lanka has been contaminated with helminth eggs [46].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate dietary intake weakens the responses of the immune system in children and increases vulnerability to infections. Several studies have been confirmed that infections were commonly diagnosed in children suffering from undernutrition [44, 45]. Another study identified that soil of the plantation sector of Sri Lanka has been contaminated with helminth eggs [46].…”
Section: Discussionmentioning
confidence: 99%
“…46.8% of infants suffering from acute diarrhea were underweight and it was worse for those children having persistent diarrhea (83.35%). [18] Respiratory infections were found to be the second common infection. [19] Measles and helminthic infections too contribute to undernutrition by increasing demand for proteins and calories but reducing its absorption and utilization.…”
Section: Determinants Of Pemmentioning
confidence: 99%
“…Antibiotic treatment can lead to various negative short‐term effects, such as vomiting, diarrhea, and anorexia 19,20 . Data from human medicine suggest that dysbiosis induced by antimicrobials is associated with an increased risk for developing asthma, postinfectious irritable bowel syndrome and chronic enteropathies such as Crohn's disease 21‐25 . Antibiotics cause prolonged intestinal dysbiosis and lead to changes in the microbial metabolism pathways in healthy dogs and humans 26‐29 .…”
Section: Introductionmentioning
confidence: 99%